Adoption of internal auditing in developing countries: Egyptian public sector - El-Tahan, Samar Yousry (AUC Knowledge Fountain, 2016)
The establishment of an independent internal audit system has become increasingly important as a means to promote governance, enhance institutional efficiency and promote public services. This research examines the extent of internal audit adoption in the Egyptian public sector. Moreover, it investigates the factors and barriers affecting this adoption and provides some solutions and recommendations for overcoming these obstacles. The study adopts qualitative methodology, as the researcher conducted in-depth semi-structured interviews with those individuals who are embedded in the process of internal auditing in Egypt. The findings highlight negative consequences of change. As the Egyptian internal auditing has a very low level of independence and qualifications of internal audit staff. In addition, the role of the internal auditors is strictly limited to financial audit and compliance with laws, where in the meantime, the modern definition of internal auditing sheds the spotlight on the performance based audit as well as it sheds the spotlight also on the financial audit. To conclude, Egypt has no any successful independent internal auditing system, and will not have any successful internal audit system, unless, the administration methodology is changed radically, once most of the focal issues have been resolved, Egypt will be able to hold a successful independent internal audit system.